The Effect Of BMI On The Incidence Of Gerd In Indonesian Citizens - M.Arif Munandar.K; M. Luthfi Parewangi; Muhammadong, Muhammadong (Sean Institute, 2024)
Gastroesophageal Reflux Disease (GERD) is becoming increasingly common in Indonesia, influenced by changes in lifestyle and dietary patterns. This study aims to explore the relationship between Body Mass Index (BMI) and the incidence of GERD in the Indonesian population. The introduction provides background on the rising prevalence of GERD and the importance of researching risk factors such as BMI. The method involves a literature review from relevant journals sourced from Google Scholar, focusing on studies investigating the correlation between BMI and GERD in Indonesia. The results of the analysis indicate that higher BMI correlates positively with an increased risk of GERD, accompanied by pathophysiological mechanisms including increased intra-abdominal pressure and dysfunction of the lower esophageal sphincter.